Pendampingan Sebagai Upaya Penggunaan Modal Kerja UMKM dalam Meningkatkan Laba Usaha: Studi pada Pengrajin Kulit Sapi RT 03 RW 07 Sukaregang Garut - Manzilatusifa, Uus; Juliantoro, Samuel Rudie; Pertiwi, Mentari Puteri (Jurnal Pengabdian Tri Bhakti, 2023)
The Community Service Program entitled "Assisting in an Effort to Use MSME Working Capital in Increasing Business Profits (Study on Cowhide Craftsmen RT 03 RW 07 Sukaregang Garut)". This activity is carried out as an effort to develop the economy in the business sector which will affect equity and increase people's income. Therefore, our Service Team will provide assistance regarding the use of working capital in increasing operating profits. Meanwhile, the benefits for business owners in the long term are to provide information about the factors that influence the increase in operating profit for Micro, Small and Medium Enterprises (MSMEs), thus making it easier for MSME owners to make decisions to increase MSME income. Keywords: Working Capital, Business Profit, Micro, Small and Medium Enterprises (MSMEs).